PRODUCTION AND MARKETING OF GOLDFISH SEED (Cyprinus Carpio) IN EAST PASAMAN REGENCY WEST SUMATERA PROVINCE - Rini, Rekian Rahma; Hendrik, Hendrik; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract               Research on production and marketing of goldfish seed (Cyprinus carpio) in East Pasaman Regency West Sumatera Province has been done in February 2018 in East Pasaman District West Sumatera Province. The purpose of this research was to know the production of goldfish seed by size and marketing of goldfish seeds. The data collection for seed cultivators and seed traders done on a Random Sampling.               Production of goldfish seeds in this area for size 2 - 3 cm in size with the amount of 240.3888.410, followed by 3 - 5 cm with the amount of 33.678.288, and 5 - 8 cm with the amount of 129.482.820 every year. Production of all seeds by 2017 were 303.100.514 goldfish seeds. This seed is produced from Rao District and South Rao District. For sized seeds 2-3 cm and 3-5 cm 90% marketed in East Pasaman area. While the seeds are sized 5-8 cm  48,84% marketed in long hydroelectric reservoirs, 27,90% on the Maninjau and 23,25% on the Rantau Berangin. Based on increasing production data, growing demand and agribusiness systems that continue to grow it can be said the marketing prospects of goldfish seeds in East Pasaman is very good. Keywords : Production, Marketing, Carp Fish Seeds, East Pasaman Regency